Desempenho parlamentar e reeleição na Câmara dos Deputados no Brasil: aspectos teóricos e empírico - Deivison Souza Cruz (2009)
This dissertation accomplishes two objectives; the first is to defend the empirical and logical connection between performance and re-election in parliament. This connection stems from the constraints and opportunities existing in the electoral and parliamentary arena amenable to measurement via construct empirically verifiable. The operation, however, depends on further studies. We mapped the possibilities, which such a study can be done. The starting point of dissent in the literature about reelection, we analyze the theoretical and methodological problems present in these disagreements over the methods proposed by various authors. If the theoretical and methodological problems are circumvented, then a better framework can best facilitate future research. We mapped the problems in terms of characterization rules vs. positive agents, arenas and institutions, and inappropriate use of statistical methods of multivariate regression as a factor hampering the measurement of the effect of performance parliamentary reelection. Based on Prospect Theory, the Theory of Rational Expectations, Theory of Tacit Knowledge, the New Institutionalism and Rational Choice Coalition Presidentialism, some solutions are proposed. Once accommodated these theories, the operation of calculating the impact of parliamentary performance on reelection become more feasible, however, as a subject for further studies.